Bridging Research Gaps in Industry 5.0: Synergizing Federated Learning, Collaborative Robotics, and Autonomous Systems for Enhanced Operational Efficiency and Sustainability - Ashraf Zia; Muhammad Haleem (IEEE Access)
Industry 5.0 marks a transformative shift in industrial operations, emphasizing human-machine collaboration, sustainability, and intelligent automation. This study conducts a Systematic Literature Review (SLR) to analyze research contributions from leading digital libraries, including IEEE, ACM, Springer, and MDPI, focusing on publications between 1992 and 2024. The objective is to identify existing research gaps, challenges, and synergies across Federated Learning (FL), Collaborative Robotics (Cobots), and Autonomous Systems (AS). From an initial collection of 12,079 papers, a core set of 92 relevant publications was selected based on predefined research questions. This review provides a structured analysis to guide scholars and practitioners in optimizing the interplay between FL, cobots, and autonomous systems, aiming to enhance adaptability, operational resilience, and environmental sustainability. By addressing unresolved challenges and highlighting emerging opportunities, this SLR contributes to bridging research gaps and supports the development of strategic frameworks that balance efficiency with sustainability, advancing the goals of Industry 5.0.